Afro-Cuban Religious Arts: Popular Expressions of Cultural Inheritance in Espiritismo and Santería - Juncker, Kristine (University Press of Florida, 2014)
This book profiles four generations of women from one Afro-Cuban religious family. From a plantation in Havana Province in the 1890s to a religious center in Spanish Harlem in the 1960s, these women were connected by their prominent roles as leaders in the religions they practiced and the dramatic ritual artwork they created. Each woman was a medium in Espiritismo-communicating with dead ancestors for guidance or insight-and also a santera, or priest of Santería, who could intervene with the oricha pantheon. Kristine Juncker argues that, by creating art for more than one religion, these wome